SISTEM KENDALI 2 HEATER GUNA MENCEGAH GUNA MENCEGAH KERUSAKAN PANEL KONTROL 150 KV DI GARDU INDUK - Rissa Amelia (Politeknik Aceh, 2021)
Control Panel is a equipment that use to regulate and manage Substations instrumentation. On the Control Panel there is a heater which functions is to heat the Control Panel room. If the heater on the control panel is damaged, the temperature humidity on the panel will increase, causing corrosion to occur at the panel terminals which is the beginning of the corona phenomenon. The cause of heater failure is because the heater works continuously to produce heat according to the maximum capacity of the heater. Therefore, based on these problems, a prototype design for a temperature monitoring tool was made on the control panel at the substation. This system can adjust the performance of the two heaters alternately heater 1 for the morning shift and heater 2 for the night shift. In addition, this system can detect damage to the heater by using a temperature sensor and then replace the heater with a heater that is still in good condition. If the temperature detected on the control panel is less than 40 ℃ then both heaters will turn on. When the temperature returns to more than 40 ℃, the heater will turn on only 1.